“Isso vem de uma aprendizagem”: discutindo o conceito de tecnologia a partir de diferentes olhares - ABREU, Fernanda Abreu de (2019)
The aim of this work is to present some conceptual definitions about the term "technology" and to analyze the uses and definitions adopted by family farmers producing manioc flour (Manihot esculenta Crantz). There are many tools selected and used during the process that goes from the production of cassava to the transportation of the flour to the marketing points. The empirical research was carried out in the Nossa Senhora de Nazaré community, located in the Abaetezinho branch, in the municipality of Abaetetuba-PA. A bibliographical research was done on the theme "technology", being fundamental the text of Vieira Pinto (2005). For the empirical work, we used the qualitative methodology, especially through interviews, having interviewed eight (8) farmers of various ages, men and women, all of them from the community itself. The main results are the diffusion of the concept of technology among the theoreticians, and also among farmers, the notions are varied, ranging from those who perceive as technologies only what is produced in industrial processes, to others who understand that their own "inventions" are technologies.